Inhibitors of histone deacetylase 1 reverse the immune evasion phenotype to enhance T-cell mediated lysis of prostate and breast carcinoma cells - Gameiro, Sofia R. (Oncotarget, 2016)
The clinical promise of cancer immunotherapy relies on the premise that the immune system can recognize and eliminate tumor cells identified as non-self. However, tumors can evade host immune surveillance through multiple mechanisms, including epigenetic silencing of genes involved in antigen processing and immune recognition. Hence, there is an unmet clinical need to develop effective therapeutic strategies that can restore tumor immune recognition when combined with immunotherapy, such as immune checkpoint blockade and therapeutic cancer vaccines. We sought to examine the potential of clinically relevant exposure of prostate and breast human carcinoma cells to histone deacetylase (HDAC) inhibitors to reverse tumor immune escape to T-cell mediated lysis. Here we demonstrate that prostate (LNCAP) and breast (MDA-MB-231) carcinoma cells are more sensitive to T-cell mediated lysis in vitro after clinically relevant exposure to epigenetic therapy with either the pan-HDAC inhibitor vorinostat or the class I HDAC inhibitor entinostat. This pattern of immunogenic modulation was observed against a broad range of tumor-associated antigens, such as CEA, MUC1, PSA, and brachyury, and associated with augmented expression of multiple proteins involved in antigen processing and tumor immune recognition. Genetic and pharmacological inhibition studies identified HDAC1 as a key determinant in the reversal of carcinoma immune escape. Further, our findings suggest that the observed reversal of tumor immune evasion is driven by a response to cellular stress through activation of the unfolded protein response. This offers the rationale for combining HDAC inhibitors with immunotherapy, including therapeutic cancer vaccines.